Lifestyle of hypertension patients who is participated in Jaminan Kesehatan Nasional (JKN) in Batang - Mutmainah Bahrun; Yayi Suryo Prabandari; Yulita Hendrartini (Berita Kedokteran Masyarakat (BKM), 2016)
PurposeThe purpose of this paper was to explore the behavior of hypertension patients who was participated in Jaminan Kesehatan Nasional (JKN) that form a lifestyle in the prevention of complications due to hypertension.MethodA qualitative-case study was conducted involving observations and depth interview to 13 hypertension patients who was participated in Jaminan Kesehatan Nasional (JKN), 2 wives and 1 husband of patients with hypertension, also 3 doctors who were BPJS partners in Batang.ResultsThe study found that first, hypertension patients in Batang knew that they were potentially affected by complications due to hypertension. Second, there was a difference in experience and behavior between hypertension patients of prolanis (program pengelolaan penyakit kronis) members and non-prolanis (program pengelolaan penyakit kronis) members. The behavior of hypertension patients of prolanis members tends to be better than non-prolanis. Third, consumption of antihypertensive drugs was preferred in the prevention of complications due to hypertension rather than improving or modifying the behavior of hypertension patients.ConclusionThe positive experience of hypertension patients during being a JKN participant of prolanis  and non-prolanis members formed a different lifestyle, also a different prevention efforts. This is due to information about hypertension that prolanis members got is better than non prolanis. JKN participants are suggested to become members of prolanis so that family doctors partner BPJS as the providers  of JKN can be more active in conveying information specifically related to hypertension and its complications. Innovative, adaptive and accessible information delivery needs to be considered in an effort to improve the lifestyle behavior of hypertension patients.